Rainfall erosion and compartments soil organic matter in coffee systems conservationist and convetional - Guimarães, Gabriel Pinto; Chaves, klinger Oliveira; Mendonça, Eduardo de Sá (Coffee Science - ISSN 1984-3909, 2015)
This study aimed to evaluate the losses of soil, water, carbon (C) and nitrogen (N) and the compartments of soil organic matter (SOM) in coffee systems belonging to the Atlantic Rainforest biome south of state of Espírito Santo. Four coffee agroecosystems were evaluated: conservationist 1 (Csv1), conservationist 2 (Csv2), conventional 1 (Conv1), conventional 2 (conv2) and field of Atlantic Forest (Mata). Evaluations of loss by water erosion under natural rainfall condition were carried from july to december 2012 and 2013. Soil samples were collected at 0-10 and 10-20 cm for evaluation of TOC, NT and compartments of SOM. The results showed that precipitation of 540,8 mm occurred during the 6 month of evaluation in 2012 promoted losses water in 1110, 2740, 6270 and 5930 mm ha-1 for Csv1, Csv2, Conv1 and Conv2, respectively, since soil losses for these respective systems were 2,87; 2,85; 152,13 and 21,17 kg ha-1. For precipitation of 669,4 mm occurred during july to december 2013 the water total losses were 203, 2900, 4750, 6270 and 8620 mm ha-1 for Mata, Csv1, Csv2, Conv1, Conv2, respectively. Conventional systems showed total average loss of 3363 g C ha-1 and 282 g ha-1 of N in the soil eroded in 2012. Conservationists systems showed C levels of microbial biomass pool 253 times higher compared to conventional systems in the 0-10 cm depth.